ACADEMIC WELL-BEING, ACADEMIC INCOMPETENCE AND IMPOSTER SYNDROME SCALE FOR UNIVERSITY STUDENTS: - Ayyıldız, Pınar; Badelzhanova , Aruzhan; Yılmaz, Adem (International Online Journal of Education and Teaching, 2024)
In this research, the goal was to create a scale measuring academic well-being, feelings of academic incompetence, and imposter syndrome among university students. The study employed the survey methodology, a quantitative research approach. It gathered perspectives from students across various Turkish universities, with 742 participants in total. The researchers designed a 5-point Likert scale featuring three dimensions and 37 items as the instrument for data collection. The analysis of the gathered data was conducted using the SPSS 24.0 and SPSS AMOS 24.0 software. Exploratory factor analysis revealed that the factor loadings varied from 0.469 to 0.882, the Kaiser-Meyer-Olkin measure was 0.912, the explained total variance stood at 67.321%, and the Cronbach's Alpha coefficient was 0.913. Confirmatory factor analysis showed the Chi-square/degrees of freedom ratio at 1.36, RMSEA at 0.04, NNFI at 0.96, SRMR at 0.03, and AGFI at 0.92. The research concluded that the developed scale was both valid and reliable, promising to be a useful tool for assessing the academic well-being, academic incompetence, and imposter syndrome feelings among college students.